LISTWAENITES IN TURKEY: PERSPECTIVES ON FORMATION AND PRECIOUS METAL CONCENTRATION WITH REFERENCE TO OCCURRENCES IN EAST-CENTRAL ANATOLIA - Uçurum, Ali (Ofioliti, 2000)
The low hydrothermal alteration of serpentinites from the ophiolite complexes in Turkey has formed listwaenites with either mineralized or non-mineralized and scattered through the three-ophiolite belts in Anatolia, Turkey. The listwaenite occurrences and associated mineralization in Turkey are reviewed, taking into account the location and description used in literature. The geology and geochemistry of the listwaenites in east central Anatolia serve as a reference to illustrate the characteristics of listwaenite formation and precious metal concentrations in ophiolite belts of Turkey. The late Cretaceous (Pre-Maastrichtian) alteration of serpentinite bodies in the Divriği and Kuluncak ophiolitic mélanges, in east central Anatolia has formed two distinct types of listwaenite. The earliest is silica-carbonate listwaenite (type I), which is dominated by silica+calcite+dolomite+ankerite±magnesite. Later, carbonate listwaenite (type II) comprise calcite+dolomite+ankerite±magnesite, and lack any significant introduction of silica. In the Divriği and Kuluncak ophiolitic mélanges the most of the silica-carbonate (type I) and carbonate (type II) listwaenite are formed along thrust fault zones. In clearly fault-related listwaenites, thrust fault(s) acted as pathway for hydrothermal fluids. In non fault-related listwaenites, hydrothermal fluids moved along highly serpentinized microfractured, stockworked and porous ultramafic rocks. The hydrothermal fluids involved in the formation of carbonate (type II) listwaenite differed from those that formed silica-carbonate (type I) listwaenite, which was enriched in SiO2, as well as CO2, Ca and H2O, whereas those that formed carbonate listwaenite were SiO2 deficient, and enriched only in CO2, Ca and H2O.